2019
DOI: 10.1039/c8gc03938k
|View full text |Cite
|
Sign up to set email alerts
|

One-pot selective conversion of C5-furan into 1,4-pentanediol over bulk Ni–Sn alloy catalysts in an ethanol/H2O solvent mixture

Abstract: The synergistic actions between an inexpensive bulk Ni–Sn(1.5) alloy, hydrogen gas, and an ethanol/H2O solvent mixture selectively assisted the one pot conversion of C5-furan compounds to 1,4-pentanediol with outstanding yields up to 92%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 58 publications
4
46
0
Order By: Relevance
“…Meanwhile, in 2-propanol/H2O solvent resulted 4.0% CPL at 87.2% conversion of FFald (entry 5). These results confirmed that the solvent significantly inhibited the C=C hydrogenation as reported previously [19,21,28]. Therefore, it can be concluded that ethanol/H2O is suitable solvent for the catalytic conversion of FFald to CPL or CPO in presence of bimetallic catalysts.…”
Section: Screening Of Solventsupporting
confidence: 90%
See 2 more Smart Citations
“…Meanwhile, in 2-propanol/H2O solvent resulted 4.0% CPL at 87.2% conversion of FFald (entry 5). These results confirmed that the solvent significantly inhibited the C=C hydrogenation as reported previously [19,21,28]. Therefore, it can be concluded that ethanol/H2O is suitable solvent for the catalytic conversion of FFald to CPL or CPO in presence of bimetallic catalysts.…”
Section: Screening Of Solventsupporting
confidence: 90%
“…The formation of FFalc was the first step then rearrangement of FFalc structure occurred on the acidic surface of bimetallic Ni-Sn alloy catalysts [20][21]. Therefore, similar approach would be applicable to the catalytic conversion of FFald over bimetallic Ni-Fe(3.0)/TiO2 catalyst.…”
Section: Kinetic Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…formic acid or acetic glacial), the use of additives is not desirable and should be avoided if possible, as suggested by Schniepp et al [10] and Leuck et al [39] Especially at relatively higher temperature and initial H2 pressure, the formation of 1,4-PeD are strongly influenced by both those parameters as shown in Figure 5 and Figure 6. Therefore, we conclude that our AlOH or -Al2O3 supported Ni-Sn(3.0) and Ni-Sn(1.5) alloy catalysts are suitable for the hydrolysis-hydrogenation reaction of 2-MeF to produce a high valuable 1,4-PeD (with yield up to 64%) product under milder reaction conditions [43].…”
Section: Kineticsmentioning
confidence: 72%
“…NH3-TPD measurements show the differences in the surface acidity (e.g., part of strong acid, >923 K) between AlOH or -Al2O3 and AC supports ( Figure 4 and Table 1). The strong acid site may able to interact with C=C bond of furan ring, protonated, and then hydrolysed in presence of ethanol/H2O [40][41][42][43]. Note to be important that over AlOH or -Al2O3 supported Ni-Sn(3.0) catalysts, no side polymerization product was observed within the reactions.…”
Section: Catalyst Screeningmentioning
confidence: 99%